2003
DOI: 10.2139/ssrn.341762
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Impact of Living Wage Laws: A Critical Appraisal of David Neumark's How Living Wage Laws Affect Low-Wage Workers and Low-Income Families

Abstract: Drawing on data from the Current Population Survey (CPS), David Neumark (2002) finds that living wage laws have brought substantial wage increases for a high proportion of workers in cities that have passed these laws. He also finds that living wage laws significantly reduce employment opportunities for low-wage workers. We argue, first, that by truncating his sample to concentrate his analysis on low-wage workers, Neumark's analysis is vulnerable to sample selection bias, and that his results are not robust t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
50
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 10 publications
0
50
0
Order By: Relevance
“…The CPS data do not provide large enough samples A third criticism is that the CPS data -which we also use in this study -do not deliver sample sizes sufficiently large to detect effects of living wage laws (Brenner et al, 2002;Pollin et al, 2008). But the calculation used to make this argument is in error.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…The CPS data do not provide large enough samples A third criticism is that the CPS data -which we also use in this study -do not deliver sample sizes sufficiently large to detect effects of living wage laws (Brenner et al, 2002;Pollin et al, 2008). But the calculation used to make this argument is in error.…”
mentioning
confidence: 97%
“…Neumark and Adams focus attention on models estimated for the workers in the bottom decile of the wage distribution. Brenner et al (2002) argued that this approach leads to spurious evidence of living wage effects, and that a quantile regression approach should be used to avoid this bias. They then estimated a quantile regression for the 10th percentile, with a striking difference in results.…”
mentioning
confidence: 99%
“…Indeed, one of the great weaknesses of the "difference-indifference" methodology is that it is unable to accurately separate the effects of different policy interventions if their timing coincides. As Brenner et al (2002) have argued, increases in the minimum wage are a much more plausible source of the effects which Neumark and Adams have attributed to living wage laws, particularly given the large number of workers earning exactly the minimum wage in their sub-sample of the CPS. Ultimately, the combination of these methodological and empirical problems makes it impossible to draw any policy conclusions, either positive or negative, from Neumark and Adams' research.…”
mentioning
confidence: 99%
“…All business assistance cities were indeed enforcing their laws in the sense that they were monitoring economic development projects to see if any fell under the strictures of the living wage law. However, except for San Antonio, TX, Brenner et al (2002) concluded that no business assistance cities had actually had a case where the law was applied to an actual business assistance recipient. 8 Unit-cost bids are typically submitted as an hourly rate for services performed, such as for security guard services or temporary office assistance.…”
mentioning
confidence: 99%
“…For example, based on a survey of city contractors in Chicago, Tolley, Bernstein, and Lesage () estimate that slightly more than one‐third of employees in covered businesses would be impacted by the living wage ordinance applied to contract workers. Finally, Brenner, Wicks‐Lim, and Pollin () find the enforcement of business assistance ordinances varies greatly between cities and question whether the actual coverage is as large as the estimates in Neumark and Adams ().…”
mentioning
confidence: 99%